2015
DOI: 10.1103/physrevlett.114.203001
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of Quantum Impurities in the Presence of a Many-Body Environment

Abstract: We develop a microscopic theory describing a quantum impurity whose rotational degree of freedom is coupled to a many-particle bath. We approach the problem by introducing the concept of an "angulon" -a quantum rotor dressed by a quantum field -and reveal its quasiparticle properties using a combination of variational and diagrammatic techniques. Our theory predicts renormalisation of the impurity rotational structure, such as observed in experiments with molecules in superfluid helium droplets, in terms of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
237
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(244 citation statements)
references
References 45 publications
7
237
0
Order By: Relevance
“…Polarons play important roles in the conduction in ionic crystals and polar semiconductors [1], spin-current transport in organic semiconductors [2], dynamics of molecules in superfluid helium nanodroplets [3][4][5], and collective excitations in strongly interacting fermionic and bosonic ultracold gases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Polarons play important roles in the conduction in ionic crystals and polar semiconductors [1], spin-current transport in organic semiconductors [2], dynamics of molecules in superfluid helium nanodroplets [3][4][5], and collective excitations in strongly interacting fermionic and bosonic ultracold gases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This results in renormalization of the molecular rotational constantthe effect previously observed for several molecules inside superfluid helium nanodroplets [9]. The angulon theory allows for a simple interpretation of such a renormalization in terms of the rotational Lamb shift [1][2][3], which is an exact phononic analogue of the photonic Lamb shift of quantum electrodynamics [10]. It was shown that even in the context of weakly-interacting ultracold gases, the magnitude of this shift is large enough to be accessible in modern experiments [11].…”
Section: Introductionmentioning
confidence: 99%
“…We consider a linear rotor molecule immersed into a superfluid, as described by the angulon Hamiltonian [1], in the presence of an external electrostatic field:…”
Section: The Angulon Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost we have to pay is that an interaction among bosons newly appears in the transformed Hamiltonian H ′ . Here we should note that a more general transformation than (14) is presented in the literature [44] for the description of a rotating impurity, so-called angulon [45], which is characterized by the transfer of the angular momentum between the impurity and the environmental bosonic degrees of freedom and by structural deformations of the bosonic distribution around the impurity. Although the system of an angulon assumes an infinite background space in contrast to our case of trapped atoms, emphasis is commonly put on the conserved quantity of the system, i.e.…”
Section: A Bogoliubov-type Approximationmentioning
confidence: 99%